Keberkesanan Penggunaan Garis Panduan Penyediaan Penginapan Pekerja Asing dalam Sektor Pembinaan - Nik Mohd Sofi, Nik Rofidah; Mohamed, Sulzakimin; Ta Wee, Seow; Kai Chen, Goh; Masrom, Md Asrul Nasid (Research in Management of Technology and Business, 2023)
In Malaysia, one challenge faced in the construction sector is how there are many foreign workers employed. This causes a lot of temporary accommodation and settlement areas being built for their use. However, these are usually built without the accordance of the approved proper specifications, building materials, and construction methods. The problem statements are regarding problems that arise due to the actions of some developers or contractors to place construction labor in buildings that are still under construction. The research objectives include finding out the effectiveness of following the accommodations preparations guidelines for the foreign workers on the construction site, identifying the factors that prevent the effectiveness of using the accommodations preparations guideline for the foreign workers on the construction site, and lastly identifying the steps to be taken to practise the usage of the accommodation’s preparation guidelines among employers. This research involved project manager, facilitation coordinators, as well as health and safety inspectors form three different construction firm as respondent.  This research used a structured interview method to study the problems arising regarding accommodations of foreign workers at construction sites, several problems highlighted include packed living arrangements, social problems, poverty, and lack of facilitating infrastructures. Based on the research study carried out, it is found that employers through the relationship between behaviors in performing a responsibility. This effectiveness is important to ensure the preparation of accommodations for foreign workers on the construction site is done properly and also ensuring the safety and health of the workers.